Frequency and predictors of cholesterol target attainment in patients with stable coronary heart disease in Belgium: results from the Dyslipidemia International Study II (DYSIS II CHD). Issue 6 (2nd November 2019) - Hermans, Michel P.; Gevaert, Sofie; Descamps, Olivier; Missault, Luc; Gillot, Bernard; De Keyzer, Dieuwke; Lautsch, Dominik; Brudi, Philippe; Ambegaonkar, Baishali; Vyas, Ami; Horack, Martin; Gitt, Anselm
ABSTRACT: Objectives : To document the frequency and predictors of low-density lipoprotein cholesterol (LDL-C) target value attainment among patients with coronary heart disease (CHD) in Belgium. Methods : The second Dyslipidemia International Study (DYSIS II) was an observational study of the prevalence of dyslipidemias and lipid target value attainment. Patients in this analysis were aged ≥ 18, had documented CHD, and had a full lipid profile. Use of lipid-lowering therapy (LLT), lipid profile, and LDL-C target value attainment (< 70 mg/dL) were assessed cross-sectionally at the enrollment visit. The distribution of LLTs was assessed among treated patients. Multivariate logistic regression was used to identify variables predictive of LDL-C target value attainment in treated patients. Results : We identified 409 patients with CHD in Belgium, 387 (94.6%) of whom were on LLT at the time of the lipid profile. Among treated patients, the rate of LDL-C target value attainment was 40.6%, and statin monotherapy was the most commonly used LLT (79.3%). Among users of statin monotherapy or combination therapy, simvastatin was the most commonly used treatment (41.6% of patients). Diabetes was associated with higher odds of LDL-C target value attainment (OR 2.29, 95% CI 1.33–3.93), and female gender was associated with lower odds (OR 0.48, 95% CI 0.24–0.97). Conclusion : Rates of LDL-C target value attainment are low in patients with CHD in Belgium. Intensifying statin therapy or combining it with non-statins is essential in Belgian patients for optimal LDL-C reduction.